Changes in serum calcium, magnesium and inorganic phosphorus levels during different phases of the menstrual cycle - Puja Dullo; Neeraj Vedi (Wolters Kluwer Medknow Publications, 2008)
Background: The menstrual cycle is a complex process involving the interaction of the hypothalamus, the anterior pituitary, the ovaries and the uterus. The hormonal changes occurring during this cyclic process not only affect oocyte maturation and the endometrial and vaginal environments but can also have an effect on a number of other physiological and biochemical phenomena. Aim and Method: We investigated the changes in serum calcium, magnesium and inorganic phosphorus levels during different phases of the menstrual cycle in fifty healthy young women. We found subtle but significant variations in these levels in the menstrual, follicular and luteal phases. Result: The serum calcium level was highest in the follicular phase whereas the serum magnesium level was lowest in the follicular phase; the serum inorganic phosphorus levels was highest in the menstrual phase. Conclusion: These variations could be due to the impact of the changing estrogen and progesterone secretion on the parathyroid glands.